Corporate Law and the Rhetoric of Choice - Greenfield, Kent (2009)
Rhetorically, the notion of choice has always been a powerful one in politics and law. This essay is intended to offer a note of caution about its use. Despite its progressive hue of individual freedom, the rhetoric of choice increasingly tends to be a notion used to defend and uphold existing matrices of economic and social power. This is because the rhetoric of choice is an excellent way to support exiting power relationships. The assertion that people acting within such power relationships are simply choosing their current situation undermines efforts to change those relationships. The powerful stay powerful; the weak stay weak. This is true in a number of areas, from discussions about school vouchers, to debates about tort reform, to the disagreements surrounding the regulation of pornography. The dependence on choice rhetoric also exists in corporate law, where the school of thought currently dominant in corporate law doctrine holds that the corporation is best seen as a voluntary arrangement among all the various stakeholders of the corporation. The rhetoric of choice is thus a powerful tool to fight against any reform of current relationships within the corporation that would embolden and empower stakeholders traditionally left out of the corporate power structure. Those involved with the corporation, whether shareholders, employees, or communities, have chosen their position, and thus should not complain when they do not receive more than what they explicitly contracted to receive. In this way, the notion of choice is used to bolster a view of corporate law that protects those already within the corporate power structure and excludes important stakeholders from corporate decision-making. The rhetoric of choice is used in the same way in corporate law discourse as it is used elsewhere by the right-to justify or bolster existing matrices of economic and social power